Case Report: Identification of a Novel Pathogenic Germline TP53 Variant in a Family With Li–Fraumeni Syndrome - Paduano, Francesco; Fabiani, Fernanda; Colao, Emma; Trapasso, Francesco; Perrotti, Nicola; Barbieri, Vito; Baudi, Francesco; Iuliano, Rodolfo (Frontiers in Genetics, 2021)
Li-Fraumeni syndrome (LFS) is an inherited autosomal dominant disease characterised by a predisposition to many cancers. Germline pathogenic variants in TP53 are primarily responsible for LFS. By performing a targeted sequencing panel in a proband with liver carcinoma having a deceased son affected by osteosarcoma, we found the novel heterozygous frameshift variant c.645del (p.Ser215Argfs*32) in the TP53 gene. This variant co‑segregated with typical LFS cancers in the family pedigree, consistent with the pathogenicity of this novel and previously undescribed TP53 variant.